Implantable defibrillator-detected heart failure status predicts ventricular tachyarrhythmias. (3rd October 2022) - Compagnucci, P; Casella, M; Bianchi, V; Giano, A; Calo', L; Bertini, M; Santini, L; Savarese, G; Santobuono, V E; Mattera, A; Lavalle, C; Amellone, C; et al.
Abstract: Background: The occurrence of ventricular tachyarrhythmias is associated with increased mortality and hospitalizations for heart failure in implantable cardioverter defibrillator (ICD) patients. Nonetheless, the temporal relationship between heart failure worsening and ventricular tachyarrhythmias has been scarcely explored so far. Purpose: We hypothesized that in patients with heart failure and reduced ejection fraction with ICDs, physiological sensor-based heart failure status, as reflected in the HeartLogic index, would predict appropriate device therapies for ventricular tachyarrhythmias (shocks and antitachycardia pacing). Methods and results: 568 patients implanted with ICDs (n=410, 72%) or cardiac resynchronization therapy-defibrillators (CRT-D, n=158, 28%) endowed with the HeartLogic algorithm were included in this prospective observational multicenter analysis. Over a follow-up of 25 [25th-75th percentile: 15–35] months, 122 (21%) patients received an appropriate device therapy (shock, n=74, 13%), while the HeartLogic index crossed the threshold value 1200 times (0.71 alerts/patient-year) in 370 subjects (65%). The occurrence of at least one HeartLogic alert was significantly associated with both appropriate shocks (HR: 2.44, 95% CI: 1.49–3.97, p=0.003) and any ICD therapies (HR: 1.95, 95% CI: 1.37–2.85, p=0.003). Using a time-dependent Cox model, the weekly IN-alert state was the strongest predictor of ICD shocks (HR: 2.94, 95% CI: 1.73–5.01, p<0.001), after correction for age, secondary prevention, and use of CRT. As compared to clinically stable subjects with no therapies, patients experiencing shocks had significantly higher baseline values of the HeartLogic index, third heart sound amplitude, and respiratory rate. Beginning about one month prior to the arrhythmic event, we noticed further increase of the combined index and the third heart sound amplitude, a decrease of thoracic impedance, and higher resting heart rate (Figure 1). Conclusions: The HeartLogic index is an independent predictor of appropriate defibrillator therapies. The combined index and its individual physiological components change well before the arrhythmic event, suggesting the existence of a window of opportunity to prevent shocks. Funding Acknowledgement: Type of funding sources: None.